PELAKSANAAN PROGRAM PROMOSI KESEHATAN DALAM PENCEGAHAN STUNTING DI PUSKESMAS - Nur, Astuti; Lestaluhu, Santi Aprilian; Mauludiyah, Zaida; Hayati, Zahratul; Marni, Marni (Ensiklopedia of Journal, 2024)
Stunting is a chronic malnutrition problem caused by insufficient nutrient intake over a long period of time due to inadequate feeding. Kampar Regency is one of the highest ranked for stunting rates in Riau Province at (31.99%). The purpose of this study was to analyze the implementation of health promotion programs in the prevention of stunting at Puskesmas Kampar Kiri Hilir. The research used an analytical qualitative method conducted at the Kampar Kiri Hilir Health Center to 3 informants including the promkes holder, the nutrition holder and the Head of the Health Center. The results showed that in general the implementation of the promkes program at the Kampar Kiri Hilir Health Center has been running, but there are obstacles such as limited budget resources in supporting the implementation of the promkes program at the Kampar Kiri Hilir Health Center. It is recommended to the Puskesmas Kampar Kiri Hilir to be used as material for evaluating the Health promotion program at Puskesmas Kampar Kiri Hilir in accordance with budget capacity.Keywords: Nutrition, Resources, Stunting